2021
DOI: 10.1007/s10877-021-00752-7
|View full text |Cite
|
Sign up to set email alerts
|

Ability of short-time low peep challenge to predict fluid responsiveness in mechanically ventilated patients in the intensive care

Abstract: Short-time low PEEP challenge (SLPC, application of additional 5 cmH 2 O PEEP to patients for 30 s) is a novel functional hemodynamic test presented in the literature. We hypothesized that SLPC could predict fluid responsiveness better than stroke volume variation (SVV) in mechanically ventilated intensive care patients. Heart rate, mean arterial pressure, stroke volume index (SVI) and SVV were recorded before SLPC, during SLPC and before and after 500 mL fluid loading. Patients whose SVI increased more than 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 33 publications
1
5
0
Order By: Relevance
“…A study in critically ill patients showed that the response of stroke volume to a systematic increase in PEEP by 5 cmH 2 O for 30 seconds detected uid responsiveness [24]. Our results con rm that volume responsiveness can be assessed by manipulating PEEP.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…A study in critically ill patients showed that the response of stroke volume to a systematic increase in PEEP by 5 cmH 2 O for 30 seconds detected uid responsiveness [24]. Our results con rm that volume responsiveness can be assessed by manipulating PEEP.…”
Section: Discussionsupporting
confidence: 75%
“…The latter study was conducted mainly in postoperative patients. Accordingly, the PEEP at baseline was low (6 cmH 2 O) [24]. Our study was conducted in a wider population of patients with circulatory failure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further tests may be used in routine: end-expiratory occlusion test (15 s lasting expiratory hold leading to increased stroke volume by 10% [ 38 ]). PEEP induced a decrease in flow parameters (14% decrease in stroke volume after the increase in PEEP by 5 cm H 2 O [ 39 ]). Some degree of fluid responsiveness may be diagnosed by performing lung recruitment—a 30% drop of stroke volume after 30 s lasting 30 cm H 2 O recruitment maneuver [ 40 ].…”
Section: Testing Fluid Responsivenessmentioning
confidence: 99%
“…In mechanically ventilated patients, positive end-expiratory pressure (PEEP) has a two-fold effect [ 13 ]: on the one hand it may increase the pulmonary vascular resistance and the right ventricular afterload by increasing the transpulmonary pressure, and on the other hand by increasing the intrathoracic pressure, it may decrease cardiac preload [ 14 , 15 ]. Considering the latter effect, a transient increase in PEEP was proposed as a volume responsiveness test in ventilated patients without low lung compliance and a low PEEP level [ 16 , 17 ]. However, in patients ventilated with high levels of PEEP and low lung compliance, the test reliability may be impaired, because increasing PEEP further may significantly increase the right ventricular afterload [ 14 ], altering the effects of PEEP changes on cardiac output.…”
Section: Introductionmentioning
confidence: 99%